Influence of radiation exposure to delayed fetal growth in wild Japanese monkeys after the Fukushima accident - Hayama, Shin-ichi; Nakanishi, Setsuko; Tanaka, Aki; Konno, Fumiharu; Kawamoto, Yoshi; Omi, Toshinori (Frontiers in Veterinary Science, 2023)
Wild Japanese monkeys (Macaca fuscata) were exposed to radiation after the Fukushima Daiichi nuclear accident in 2011. To clarify the biological effects of radiation exposure on their fetal growth, pregnant monkeys and their fetuses were analyzed. These animals were collected between 2008 and 2020 (before and after the accident in 2011) living in Fukushima City, approximately 70 km from the nuclear power plant. Multiple regression analyses were conducted with fetal body weight (FBW) and fetal head circumference (FHS) as objective variables, and maternal and fetal factors as explanatory variables. The maternal factors were relative exposure dose rate (REDR), age, body weight, body length, fat index, and parity. The fetal factors were crown ramp length (CRL) and sex. Multiple regression analyses showed that FBR and FHS growth were positively associated with CRL, maternal body length, and negatively associated with REDR. Since the relative growth of FBR and FHS to CRL decreased with increasing REDR, radiation exposure due to the nuclear accident may have contributed to the delayed fetal growth observed in Japanese monkeys.